Chlorophyllase (PsCLH1) and light-harvesting chlorophyll a/b binding protein 1 (PsLhcb1) and PsLhcb5 maintain petal greenness in Paeonia suffruticosa ‘Lv Mu Yin Yu’ - Qing Hao; Tongtong Li; Gaojie Lu; Shuo Wang; Zhen Li; Cancan Gu; Fan Kong; Qingyan Shu; Yang Li (Journal of Advanced Research)
Introduction: Green flowers are not an adaptive trait in natural plants due to the challenge for pollinators to discriminate from leaves, but they are valuable in horticulture. The molecular mechanisms of green petals remain unclear. Tree peony (Paeonia suffruticosa) is a globally cultivated ornamental plant and considered the ‘King of Flowers’ in China. The P. suffruticosa ‘Lv Mu Yin Yu (LMYY)’ cultivar with green petals could be utilized as a representative model for understanding petal-specific chlorophyll (Chl) accumulation and color formation. Objectives: Identify the key genes related to Chl metabolism and understand the molecular mechanism of petal color changes. Methods: The petal color parameter was analyzed at five developmental stages using a Chroma Spectrophotometer, and Chl and anthocyanin accumulation patterns were examined. Based on comparative transcriptomes, differentially expressed genes (DEGs) were identified, among which three were functionally characterized through overexpression in tobacco plants or silencing in ‘LMYY’ petals. Results: During flower development and blooming, flower color changed from green to pale pink, consistent with the Chl and anthocyanin levels. The level of Chl demonstrated a similar pattern with petal epidermal cell striation density. The DEGs responsible for Chl and anthocyanin metabolism were characterized through a comparative transcriptome analysis of flower petals over three critical developmental stages. The key chlorophyllase (PsCLH1) and light-harvesting chlorophyll a/b binding protein 1 (PsLhcb1) and PsLhcb5 influenced the Chl accumulation and the greenness of ‘LMYY’ petals. Conclusion: PsCLH1, PsLhcb1, and PsLhcb5 were critical in accumulating the Chl and maintaining the petal greenness. Flower color changes from green to pale pink were regulated by the homeostasis of Chl degradation and anthocyanin biosynthesis. This study offers insights into underlying molecular mechanisms in the green petal and a strategy for germplasm innovation.